PP56 Prevalence of Chronic Kidney Disease in Ethnic Minority Groupings: Findings from the Health Surveys for England 2003 and 2004. (10th September 2013) - Aitken, G; Moon, G; Roderick, P J
Abstract : Background: In the UK, people from South Asian and Black communities have higher rates of Renal Replacement Therapy (RRT) compared to the White population. It is not clear why ethnic minorities have such high rates: possibilities include a higher prevalence of Chronic Kidney Disease (CKD) or a faster rate of progression to End Stage Renal Failure (ESRF). This study aimed to examine ethnic variation in the prevalence of CKD by a range of socio-economic, clinical and measurement characteristics. Methods: The 2003 and 2004 Health Surveys for England were combined, totalling 9970 individuals aged over 16 with a valid serum creatinine value. Ethnicities were grouped into three categories; White, South Asian and Black. Prevalence of CKD stage 3–5 was calculated using the more accurate Chronic Kidney Disease Epidemiology Collaboration (CKDEPI) estimating equation. Binomial logistic regression models (multivariate and stepwise selection) were used to determine the associations of ethnicity with CKD adjusted for socio-economic, health and clinical measurement factors. Results: Prevalence of CKD stage 3–5 for White individuals was 7.6%, for South Asian was 2.8% and for Black was 4.9%. CKD prevalence increased consistently for White individuals by age grouping; the rate of increase was different for Black and South Asian individuals. Black and South Asian CKD prevalence was higher than Whites for those aged 35-54 and Black CKD prevalence was approximately double that of South Asian for ages 55-74. CKD 3–5 was strongly associated with nearly all covariates for White ethnicity, less so for South Asian and Black individuals. Odds Ratios for South Asian and Black were far higher than White for selected associated covariates. Adjustment for age and other covariates only produced only one statistically significant difference; an age-sex adjusted model confirming South Asian with lower risk of CKD compared to White (OR 0.64 [95% CI 0.44, 0.92]). Conclusion: South Asian and Black ethnicities have lower CKD prevalence compared to White, but there is evidence of higher CKD prevalence in younger age groupings for South Asian/Black participants. Lack of statistical difference when adjusting for age and wide confidence intervals for minorities imply further research is needed with a larger sample size of ethnic minority groupings.